Kelimpahan dan Pola Penyebaran Nematoda Entomopatogen sebagai Agensia Pengendali Serangga Hama pada Berbagai Lahan di Semarang - Dyah Rini Indriyanti; Arini Dwi Hutami Pribasari; Desi Puspitarini; Priyantini Widiyaningrum (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The soil was a place which plants and various organisms live. One of the soil organisms that plays an important role as agents of biological control of parasitic nematodes of insects, was known by entomopathogenic nematodes (ENP’s). The aims of this research was analyzing the population density and patterns spread of the entomopathogenic nematodes on overgrown annuals land, overgrown perennial land, non-vegetation land and ranch land. The experimental design used in this study was a randomized design group. The technique of determining location using purposive sampling. Soil samples were taken at four location with eight replicates. The research was held in August-October 2013. The ENP’s of land obtained by the technique of baiting using Tenebrio molitor. The result showed that ENP’s population density was found from ranch land was 67.411 tail/mL. It was higher than the ENP’s population density on non-vegetation land was 15.199 tail/mL. The statistics Mann Whitney showing absence of difference density of populations ENP’s. A pattern to scatter nematode entomopathogen on some land widely distributed in clumped.